A Disorder by Any Other Name: Metacognition, Schizophrenia, and Diagnostic Practice. (January 2019) - Lysaker, Paul H.; Zalzala, Aieyat B.; Ladegaard, Nicolai; Buck, Benjamin; Leonhardt, Bethany L.; Hamm, Jay A.
Humanistic psychology has made us aware that any understanding of schizophrenia must see persons diagnosed with this condition as whole persons who are making sense of what wellness and recovery mean to them. This has raised questions about what the diagnosis of schizophrenia means and whether the diagnostic label of schizophrenia is helpful when we try to conceptualize the actions and aims of treatment. To examine this issue we propose it is essential to consider what is systematically occuring psychologicaly in recovery when persons experience, interpret and agentically respond to emerging challenges. We then review how the integrated model of metacognition provides a systematic, person-centered, evidence-based approach to understanding psychological processes which impact recovery, and discuss how this guides a form of psychotherapy, metacognitive reflection and insight therapy, which promotes metacognitive abilities and support recovery. We suggest this work indicates that metacognitive capacity is something that can be diagnosed without stigmatizing persons. It can be used to meaningfully inform clinical practice across various theoretical models and offers concrete implications for rehabilitation.